Critical Success Factor Model for the Implementation of Information System in Institutions of Higher Learning in Indonesia - Haerani, Reni (2024)
The successful adoption of information systems in institutions of higher learning is a critical factor in enhancing the efficiency, productivity, and competitiveness of institutions higher learning in the digital age. However, the influence of organizational culture, particularly hierarchical culture, on the success of information system adoption remains a complex and underexplored area, especially in the context of institutions higher learning Banten Province, Indonesia. The problem with implementing information systems in private universities is the need for more quality, and the role of the information system has not been optimal in supporting institutional operation, so it does not produce the information needed by top management as a basis for decision- making. This research introduces a critical success factor model for the implementation of information system adoption in institutions of higher learning within the region. The success of an Information System (IS) measurement is a step of extended evaluation as it consists of some steps and dimensions used. Organizational hierarchical support is needed to secure funding. It provides a referral strategy and supports the entire Information System (IS) effort and its implementation to ensure the realization of objectives. This research assessed the hierarchical culture that prevails in institutions of higher learning in Banten Province using surveys, interviews and content analysis. This study also investigated how this culture impacts the success of information system adoption, considering system use, use satisfaction, and system effectiveness. The proposed model integrates organizational hierarchical culture theory elements and DeLone and McLean’s model for adopting information systems successfully. The proposed model combines organizational hierarchical culture theory elements and DeLone and McLean’s theory of successfully adopting information systems. It aims to provide an understanding of the relationship between organizational hierarchical culture and the successful implementation of information systems in the context of institutions of higher learning in Banten Province, Indonesia. The questionnaire was distributed to university leadership respondents using a Google Form link with confirmed reliability and validity. Structural Equation Modeling (SEM) using SmartPLS version 3 software was used to present the data. SEM path analysis shows the central construct relationships in the data. The results obtained from this research indicate the influence of hierarchical culture in organizations on the success of information systems in institutions of higher learning in Banten Province, Indonesia. This research provides a comprehensive picture of organizational hierarchical culture’s influence on the success level in evaluating information systems in higher learning. The proposed model can become a reference for future research, especially at universities where researchers combine the success of information systems and contribute to the progress of higher learning in this new area.